Demographic, Clinical, and Health System Characteristics Associated With Pain Assessment Documentation and Pain Severity in U.S. Military Patients in Combat Zone Emergency Departments, 2010–2013. Issue 5 (September 2016) - Blackman, Virginia Schmied; Cooper, Bruce A.; Puntillo, Kathleen; Franck, Linda S.
Abstract : Emergency department (ED) pain assessment documentation in trauma patients is critical to ED pain care. This retrospective, cross-sectional study used trauma registry data to evaluate U.S. military combat zone trauma patients injured between 2010 and 2013 requiring ≥ 24-hr inpatient care. Study aims were to identify the frequency of combat zone ED pain assessment documentation and describe pain severity. Secondary aims were to construct statistical models to explain variation in pain assessment documentation and pain severity. Pain scores were documented in 60.5% ( n = 3, 339) of the 5, 518 records evaluated. The proportion of records with ED pain scores increased yearly. Pain assessment documentation was associated with documentation of ED vital signs, comprehensive facility, more recent year, prehospital (PH) heart rate of 60–100 beats/min, ED Glasgow Coma Scale score of 15 vs. 14, blunt trauma, and lower injury severity score (ISS). Pain severity scores ranged from 0 to 10; mean = 5.5 ( SD = 3.1); median = 6. Higher ED pain scores were associated with Army service compared with Marine Corps, no documented PH vital signs, higher PH pain score, ED respiratory rate < 12 or >16, moderate or severe ISS compared with minor ISS, treatment in a less-equipped facility, and injury in 2011 or 2012 vs. 2010. The pain severity model explained 20.4% of variance in pain severity. Overall, frequency of pain assessment documentation in combat-zone EDs improved yearly, but remained suboptimal. Pain severity was poorly predicted by demographic, clinical, and health system variables available from the trauma registry, emphasizing the importance of individual assessment.